The definition and the different approaches of green economy (Journal of Universal Science Research, 2023)
Various economists stress different arrangements to manage the transition toward a green economy. Some suggest government policy makers utilize subsidies or regulations to guide the private sector toward environmentally friendly decision-making. Others argue more roundabout incentives will empower companies to take a more environmentally friendly approach. A green economy is an economy that aims at reducing environmental risks and ecological scarcities, and that aims for sustainable development without degrading the environment. It is closely related with ecological economics, but has a more politically applied focus. The 2011 UNEP Green Economy Report argues "that to be green, an economy must not only be efficient, but also fair. Fairness implies recognizing global and country level equity dimensions, particularly in assuring a Just Transition to an economy that is low-carbon, resource efficient, and socially inclusive."